2012
DOI: 10.1186/1471-2458-12-910
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of education level and dairy fat sources to serum cholesterol in Russian and Finnish Karelia: results from four cross-sectional risk factor surveys in 1992–2007

Abstract: BackgroundFood habits vary by socio-economic group and geographic area. Data on socio-economic differences in food habits and in serum total cholesterol concentration from Russia are scarce. Our aim was to examine changes and educational differences in serum total cholesterol and in the consumption of major sources of saturated fat in two geographically neighbouring areas, Russian and Finnish Karelia, and to examine whether the foods associated with serum total cholesterol are different in the two areas.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(21 reference statements)
0
2
1
Order By: Relevance
“… 27 Recent studies from Scandinavia have presented data up to 2010 and found stable 28 or diminishing 7 , 29 educational inequalities in cholesterol levels as well as a levelling off. 30 We found no differences according to education among men, and the higher cholesterol initially noted among women with low education were not present in 2014. This is encouraging and supports the joint efforts of society and health care in achieving a healthier life style and that they have also reached deprived groups.…”
Section: Discussioncontrasting
confidence: 60%
“… 27 Recent studies from Scandinavia have presented data up to 2010 and found stable 28 or diminishing 7 , 29 educational inequalities in cholesterol levels as well as a levelling off. 30 We found no differences according to education among men, and the higher cholesterol initially noted among women with low education were not present in 2014. This is encouraging and supports the joint efforts of society and health care in achieving a healthier life style and that they have also reached deprived groups.…”
Section: Discussioncontrasting
confidence: 60%
“…High or low CD14 expression has been suggested to interact with environmental exposure to endotoxin (LPS), thereby precipitating allergic phenotypes (8,25). Furthermore, burden of viral infections, exposure to fungi, diet, parental smoking behaviour and other socio-economic factors also vary between the two populations (26)(27)(28)(29)(30)(31)(32)(33). All these factors may not only influence the allergic phenotype but also have an effect on DNA methylation thus contributing to the observed inconsistent methylation patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, a high CQI is likely to represent a high intake of dietary fiber, which can lower cholesterol levels, 46 and a high level of education had the same effect. 47 While a lower cholesterol level was detrimental to male fertility. 48–50 For instance, a large-scale study of 7601 general men in China suggested that a higher cholesterol level was correlated with better sperm motility.…”
Section: Discussionmentioning
confidence: 99%